1994
DOI: 10.1093/infdis/170.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Shock Syndrome Toxin 1 Contributes to the Arthritogenicity of Staphylococcus aureus

Abstract: Although enterotoxins have been implicated in disease states such as food poisoning and toxic shock syndrome, their role in infectious arthritis is not known. To study the arthritogenic properties of toxic shock syndrome toxin 1 (TSST-1), two pairs of S. aureus strains isogenic for TSST-1 production were injected intravenously into healthy Swiss mice. Mice injected with TSST-1-secreting staphylococcal strains developed more frequent and more severe arthritis than did mice inoculated with the isogenic TSST-1-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…First, the study was performed using a USA300 strain, which is the predominant S. aureus isolate that causes CA-MRSA infections in the United States. However, prior work found that USA200 S. aureus strains producing toxic shock syndrome toxin-1 (TSST-1) can cause hematogenous and osteomyelitis infections (48,49). Because USA200 strains produce little or no AT because of a stop codon in the AT gene (50), the anti-AT mAb will likely not have an effect in USA200 or in other strains that do not produce AT.…”
Section: Resultsmentioning
confidence: 99%
“…First, the study was performed using a USA300 strain, which is the predominant S. aureus isolate that causes CA-MRSA infections in the United States. However, prior work found that USA200 S. aureus strains producing toxic shock syndrome toxin-1 (TSST-1) can cause hematogenous and osteomyelitis infections (48,49). Because USA200 strains produce little or no AT because of a stop codon in the AT gene (50), the anti-AT mAb will likely not have an effect in USA200 or in other strains that do not produce AT.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, microbial superantigens can be arthritogenic because TSST-1 is known to exacerbate bacterial cell wall-induced arthritis in rats [35]. TSST-1 also plays a pivotal role in the development of septic arthritis in mice because the frequency and severity of arthritis are increased in mice injected intravenously with TSST-1-secreting S. aureus [36]. In humans, S. aureus is the causative agent in about 60% of non-gonococcal bacterial arthritis cases [13].…”
Section: Discussionmentioning
confidence: 99%
“…The infected mice displayed increased levels of inflammatory cytokines, such as tumor necrosis factor and interleukin-6 (IL-6) in serum (7). We have also shown that toxic shock syndrome toxin 1 (TSST-1), a superantigen produced by S. aureus LS-1, contributes to the arthritogenicity of S. aureus (3,5). A series of studies using this model suggested that S. aureus arthritis is a T-cell-dependent and superantigen mediated disease.…”
mentioning
confidence: 97%